Radioactive discharge from patients with thyroid cancer under 131I treatment and its safe disposal to the public sewer system - Bagher Tavakoli, Mohamad (Contemporary Oncology/Współczesna Onkologia, 2005)
Introduction: The treatment of thyroid cancer using unsealed sources of radioactive materials is usually associated with a large amount of 131 I. The major problem for hospital treatment of these patients is the disposal of waste which requires special protection. Materials and methods: 152 patients with thyroid cancer admitted to the nuclear medicine department of Said Al-Shohada Hospital for 131 I treatment were studied. Exposure from patients was measured using a Victorian 190F survey dosimeter. 131 I excreted from these patients during isolation was calculated. Results: More than 70% of administered 131 I was excreted after 24 hours, 90% after 48 hours and 96% after 72 hours of the isolation. The mean biological half-life of 131 I in patients with thyroid cancer was found to be 13.9±1.9 hours. There was no significant difference between the mean effective half-life in patients treated for the first time and the second time at 95% significant level. Conclusions: The results of this study showed that the difference in the discharge rate of 131 I from patients with thyroid cancer receiving first and second treatment was not significant. The mean discharge rate after the first 24 hours was more than 70%, and it was more than 96% after the third 24 hours of drug administration. The results can be used to design a safe collecting and discharge method of the waste.